Etika Sufistik: Studi Pemikiran Jalaluddin Rakhmat - Naibin, Naibin (Universitas Islam Tribakti Lirboyo Kediri, 2024)
The purpose of this article is to discuss the thoughts of Jalaluddin Rakhmat. This article focuses on discussing Jalaludin Rakhmat's views on the idea of ​​ethics and his Sufi views. Jalaluddin Rakhmat's anxiety arose from seeing the phenomenon of piety being measured by fiqh rather than by ethics. As an urban Sufi figure, he offers a new paradigm in understanding Islamic doctrine. Avoiding evil is the initial foundation of piety, and worship is the second foundation. This research is library research using the content analysis method. The study results show that Jalaluddin Rakhmat's ethical concept is more on religious ethics, where the Quran, Sunnah, and ushul fiqh are the sources. In contrast, his Sufism thoughts are more on moral Sufism thoughts. These two sciences are the foundation for the birth of Sufi ethical thoughts.